Strut and tie models with the dual use of the finite element method and the lattice networks - Isikli, Yunus; Binici, Baris; Arici, Yalin; Tuncay, Kagan (Engineering structures, 2026)
Strut and tie modelling (STM) is widely recognized as a prominent design method for the design of disturbed (D) region reinforced concrete structural elements. The paramount initial step in conducting optimized reinforcement designs lies in the establishment of strut and tie geometry. In this study, a novel dual modelling approach is proposed, combining two distinct models, namely the continuum model (specifically, a finite element model) and the lattice network (comprising overlapping truss elements interconnected at every two nodes). The approach involves the application of a novel element removal algorithm based on the computed internal forces and stresses for the two lattice and finite element models working in tandem while sharing information. The iterative process continues until the convergence of the internal energy of the reduced lattice network. To evaluate the accuracy and efficacy of the proposed approach, a comprehensive demonstration is conducted employing the 20 most extensively studied design examples documented in the literature. The findings indicate that the dual system is a viable alternative method for STM design by satisfying the minimum energy requirements and without conducting laborious nonlinear finite element analysis. Furthermore, objective designs are possible from the derived STM models which can used in automated design flows. •A novel optimization method is developed for strut-and-tie modeling.•The method integrates finite element analysis with lattice networks.•The approach is tested on 20 different structural members.•Results demonstrate improved accuracy and efficiency in structural design.•The study provides a significant contribution to the literature on reinforced concrete modeling.